Implementing Extensive Reading with Wattpad to Improve English Students Reading Comprehension at Senior High School Level - Paringja, Mutia Khairunnisa; Fatriana, Nina (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Reading comprehension is important, but low interest among middle school students has led to further research. Using the extensive reading method with Wattpad can improve students’ reading skills significantly. This research aims to improve middle school students’ reading comprehension by integrating Wattpad as a learning medium, offering an alternative method in English language education. This research uses statistical analyzes such as normality, homogeneity, Howell game post hoc, and Welch’s test. This research used a quasi-experimental design with the experimental group using Wattpad and the control group using traditional methods. A quasi-experimental design was chosen because there are external variables that are beyond the researcher’s control. The research subjects consisted of two groups: the experimental group received extensive reading treatment with Wattpad, and the control group used traditional methods. . Analysis of this research data confirms the effectiveness of extensive reading with Wattpad. Statistical tests show normality, homogeneity, and significant differences between the experimental group and the control group. These findings are in line with previous research which shows that extensive reading significantly improves students’ comprehension skills. In conclusion, this research provides strong evidence that extensive reading with Wattpad has a positive impact on comprehension student reading.